Implementing the Global Goals in City Regions. (May 2016) - Head, Peter
This article describes the vision as well as the details behind a new open source digital planning platform named, resilience.io that is designed to support disaster risk reduction and management, delivery of the Global Goals, deep decarbonisation, and connecting financing opportunities to projects that are inclusive, resilient, and sustainable. Drawing from the experience of a lifetime on urban practice in infrastructure and planning, this informational gateway is designed to document the material, topographic and process world of urban transformation as well as to influence institutional decisions to adopt resilient processes and outcomes. This intends to contribute to the global initiative to bring economic success to a world in which human well-being is improved while using resources in a resilient way and where resource use is circular and regenerative. At the heart of the resilience.io systems model are the links between ecology, resources and human well-being.